PERANCANGAN PROGRAM PENGGAJIAN KARYAWAN KOPERASI - Handini Widyastuti; Widyastuti, Handini; Siahaan, Fernando; Niyanti, Niyanti (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2021)
The computerized role of an Employee Cooperative in managing data into useful information is needed. One that needs to be considered in an Employee Cooperative for the welfare of its employees is management in the payroll sector. With the salary earned, employees can fulfill their daily needs. Employee payroll system processes carried out at Employee Cooperatives still use a manual system, starting from recording and calculating salaries to receiving salaries for employees, thus allowing errors in the employee payroll process. In addition, there is a buildup of data processing that must be recorded or processed repeatedly to get the data of each employee in an effort to compile reports on the results of employee payroll each month. A program can be an alternative problem solving in processing employee payroll data. With the existence of a well-computerized payroll system, it can avoid the occurrence of errors in the calculation of salary so that the payment of employee salaries can be paid on time. Therefore, with the design of this cooperative employee payroll program, it is made so that the payroll system is better than before.